The Chilean social crisis and mental health: a glance from the life cycle - Barrera-Herrera, Ana (2022)
During 2019, Chilean society witnessed massive citizen demonstrations motivated by historical inequalities. The objective of this study is to compare the perception of young adults and adults about the social protests and its relation to mental health and social well-being. 711 people answered the online survey on the study factors. The results indicate that adults above the age of 30 show more interest in politics and both groups categorically reject the use of violence during the civilian protests. Moreover, the young adults showed higher results in anomie and negative affectivity, whereas adults show better social well-being and satisfaction with live. The Chilean social protest has had political and socio-emotional consequences, which remain until today.